2016
DOI: 10.1007/5584_2016_27
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in Food and Animals: A Comprehensive Review

Abstract: Zoonoses are infections or diseases that can be transmitted between animals and humans through direct contact, close proximity or the environment. Clostridium difficile is ubiquitous in the environment, and the bacterium is able to colonise the intestinal tract of both animals and humans. Since domestic and food animals frequently test positive for toxigenic C. difficile, even without showing any signs of disease, it seems plausible that C. difficile could be zoonotic. Therefore, animals could play an essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 172 publications
(123 reference statements)
8
64
0
Order By: Relevance
“…C. difficile is particularly prevalent in production animals such as piglets and calves both in Australia (Knight et al, 2014, 2016) and other countries (Hensgens et al, 2012; Rodriguez et al, 2016). Furthermore, genetically similar strains of C. difficile (characterized by RT, MLST, MLVA, and WGS), particularly toxinotype V (RT078), have been recovered from humans, production animals and retail meat, fuelling speculation that CDI may have a foodborne or zoonotic etiology (Rupnik and Songer, 2010; Knetsch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C. difficile is particularly prevalent in production animals such as piglets and calves both in Australia (Knight et al, 2014, 2016) and other countries (Hensgens et al, 2012; Rodriguez et al, 2016). Furthermore, genetically similar strains of C. difficile (characterized by RT, MLST, MLVA, and WGS), particularly toxinotype V (RT078), have been recovered from humans, production animals and retail meat, fuelling speculation that CDI may have a foodborne or zoonotic etiology (Rupnik and Songer, 2010; Knetsch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The predisposing factors associated with C. difficile infection (CDI) in dogs remain largely unknown. Antibiotic therapy is, so far, the only known risk factor for C. difficile colonization in dogs [8,9]. In the present work, five cases of chronic-recurring diarrhea in dogs with CDI have been reported.…”
mentioning
confidence: 61%
“…C. difficile has been reported in some studies to be one of the possible bacterial agents [2,4e6], although no studies to date have confirmed this hypothesis [3]. It is recognized that disruption of the gut microbiota is the main predisposing factor for colonization by C. difficile [8], and recent studies have shown dysbiosis in dogs with many gastrointestinal diseases including chronic diarrhea [15]. One known consequence of gut dysbiosis is alteration in bile acids, which can facilitate the germination of C. difficile spores [16,17].…”
mentioning
confidence: 99%
“…In these studies, the prevalence of strains of C. difficile associated with illness in hospitalized patients varied from high, predominantly in North America, to lower figures, usually in Europe. The common RTs from animal studies have been found in meat, suggesting that the contamination is occurring somewhere during processing, rather than from another external source (Rodriguez et al, 2016). Contamination of meat likely results from gut content spillage during evisceration or perhaps accumulation of spores within abattoir environment (Houser et al, 2012).…”
Section: Difficile In Food Animals and Foodborne CDImentioning
confidence: 99%
“…Although there are few studies on the prevalence of C. difficile in sheep and goats (0-8.5%) Avberšek et al, 2015;Rodriguez et al, 2016), the available literature does not suggest that they pose a major risk of CDI in humans.…”
Section: Difficile In Goats and Sheepmentioning
confidence: 99%